Distinct cognitive and neuropsychiatric features of amnestic dementia with comorbid Alzheimer's and TDP‐43 proteinopathies. (31st December 2021) - Kochheiser, Makayla L; Kawles, Allegra; Minogue, Grace; Keszycki, Rachel M.; Riley, Michaela; Mao, Qinwen; Flanagan, Margaret E; Mesulam, Marsel; Geula, Changiz; Weintraub, Sandra; Gefen, Tamar
Abstract: Background: Inclusions containing phosphorylated transactive response DNA‐binding protein 43 (TDP‐43) aggregates have been shown to coexist in ∼60% of cases with postmortem Alzheimer's disease (AD) pathology, typically confined to mediotemporal brain regions. Together, these comorbid proteinopathies (TDP/AD) can lead to an amnestic dementia syndrome. The goal of this study was to identify, at early symptom onset, the shared versus distinct clinical, neuropsychological, and psychiatric features of cases with amnestic dementia and comorbid TDP/AD compared to those with AD as the primary neuropathologic diagnosis. Method: Twenty‐six individuals with amnestic impairment (Memory CDR=0.5 or 1) were identified from the Northwestern Alzheimer's Disease Research Center and stratified by the presence of either postmortem AD pathology (N=13) or comorbid TDP/AD (N=13). Neuropsychological scores from tests of attention, language, executive functioning, visuoconstructional abilities, and mood/neuropsychiatric symptoms were analyzed from the NIA's Uniform Data Set, version 2.0 or 3.0. Verbal (narrative and list‐learning) encoding and recall, and visual recall were included in memory assessment. In a subset of cases, a "visual‐to‐verbal" recall score was computed to determine the relative strength of visual memory compared to verbal. Student t‐tests with Welch's correction were used to determine differences between groups. Result: There were no differences in age at onset or death, frequency of APOE‐4 allele, or years of education between clinical groups. Preliminary findings showed no differences in attentional, executive, language, or visuoconstructional abilities. However, at disease onset, the TDP/AD group showed substantially higher frequency and severity of neuropsychiatric symptoms, including depression (p<0.005). Memory testing showed no group differences at the levels of learning/encoding verbal information; however, the TDP/AD group performed significantly worse in long‐term recall for narrative information (p<0.05). Qualitatively, the TDP/AD group showed stronger visual recall abilities (relative to verbal), whereas the AD group showed comparable performances in recall of material‐specific information. Conclusion: Preliminary findings suggest that comorbid TDP/AD underlying amnestic impairments demonstrate a distinct cognitive and neuropsychiatric phenotype at disease onset. These findings help lay the groundwork for future in‐depth clinicopathologic studies and can help guide proper diagnosis of multiple etiology amnestic dementia.